ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHA PETERNAKAN AYAM PETELUR DI KABUPATEN LIMA PULUH KOTA - Wardhana, Hardiyan; Alfikri; Nofrianil; Iryani, Nelvia (Ekonomipedia: Jurnal Ekonomi Manajemen dan Bisnis, 2023)
The laying chicken business has developed very rapidly, but the community does not know much and understands about the factors that influence the production of chicken farms. The purpose of this study is to determine the income and the factors that influence income in Lima Puluh Kota Regency is feasible or not. The method of determining respondents by the census method. Data analysis method uses agriculture analysis and multiple linear regression. The results showed that the total costs incurred by laying hens with an average of Rp. 2,147,620,427/ Period. The number of laying hens was obtained with an average value of Rp2,483,324,612 / Period. By using multiple linear regression analysis obtained the results of the study showed a coefficient of determination (R2) of 99.4%. The f test results were carried out with the result of sig 0.00 < 0.05 which means that the independent variables simultaneously affected income. T test results can be seen that the value of sig t where significant results obtained with a value of sig < 0.05 for the variable cost of seeds (X1) is 0.990, feed costs (X2) is 0,000, the cost of vitamins (X3) is 0.009, costs of cages (X4) is 0,000, and labor costs (X5) are 0,000, it can be concluded that the variables that have a partial influence on income are the variable costs of feed, vitamin costs, pen costs and labor costs.